Factors influencing successful implementation of Biosphere Reserves in Vietnam: Challenges, opportunities and lessons learnt. Issue 67 (January 2017) - Cuong, Chu Van; Dart, Peter; Dudley, Nigel; Hockings, Marc
Highlights: Vietnam Biosphere Reserves theoretically follow the Seville guidelines but have weak management practice. Biosphere Reserve management and communication efforts focus on conservation of the core protected area zone. Top-down, sectoral interests hinder effective delivery of the biosphere reserve approach. Strong province and sector leader engagement contributes to long-term biosphere reserve success. Abstract: The way biosphere reserve principles are applied in Vietnam was assessed through analysis of legal documents and an online survey with 41 managers and staff members of the Biosphere Reserve Management Boards and National Man and the Biosphere Committee. The significant growth of the biosphere reserve network in Vietnam since 2000 is indicative of strong support from the National MAB Committee and the local provincial authorities in particular. Although all biosphere reserves conform to the Biosphere Reserve conceptual model, the operation and management effectiveness of sites is hindered by the predominant practice of sectoral and top-down control that is at odds with the intent of biosphere reserve management. The relatively weak legal status of biosphere reserves within the national framework is counter balanced by their more direct management by, and support from the autonomous provincial and city authorities. Recent administrative decentralisation in Vietnam allows the local authority flexibility in interpreting the central policies and regulations so as to benefit biosphere reserve management. Future sustainability and effectiveness of the biosphere reserves will depend on the implementation of appropriate, locally-based management solutions. This will require stronger support and commitment of the provincial leaders, relevant sectoral actors and communities to ensure cross-sectoral participation and collaboration, and secure adequate resourcing of biosphere reserve management activities.